FAKTOR-FAKTOR PENGHAMBAT BELAJAR RENANG PADA SISWA KELAS X DI SMA NEGERI 1 MUARA ENIM - Amalia Barikah (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2018)
This study was aimed to determine theinhibiting factors of swimming exercise of eighth grade students at State Senior High School 1 Muara enim. This study was descriptive research with survey methods. The data collection technique used was questioners. The questioners were determining the internal and external factors including 29 items.  The population was Ten grade students at State senior High School 1 Muara enimtotaling of 130 students. Data analyses technique used was descriptive analyses. The results indicatedthat theinhibiting factors of swimming exercise of Ten grade students at State Senior High School 1 Muara enimwere 9 students (6,9%) had very high category, 22 students (16,9%) had high category, 56 students (43,1%)  had medium category, 40 students (30,8%) had low category and 3 students (2,3%) had very low category. Keywords: inhibiting factors, swimming exercise, students